PENGAWETAN IKAN LAYANG (Decapterus russelli) SEGAR MENGGUNAKAN EKSTRAK RUMPUT LAUT (Caulerpa racemosa) - Saul A. Serpara; Selfia M. Nara (Universitas Musamus, Merauke, Papua, 2016)
This study aims to determine the effect of using seaweed extract Caulerpa racemosa to scads fish (Decapterus sp.) quality by organoleptic testing (texture, gills, eye and smell) and microbiology score (TPC) by using 2 (two) treatments, that is seaweed extract (A): using extract and without extract and storage time (B): 0 hour, 12 hour, 24 hour, 36 hour and 48 hour. The organoleptic score range between 5.25 for using seaweed treatment until 4.50 for without using seaweed treatment on the 48th hour. Fish gills organoleptic score range between 5.56 for using seaweed treatment until 4.30 for without treatment on the 48th hour. The eye organoleptic score range between 5.63 for using seaweed treatment until 5.25 for without seaweed treatment on the 48th hour. The smell organoleptic score range between 5.58 for using seaweed extract until 4.45 for without seaweed treatment on the 48th hour. Analysis of variance showed that the organoleptic score by using seaweed extract, without seaweed extract, storage time and interact between the both gives the real effect. Based on Indonesia National Standard (SNI 01-2729-1991) that, the maximum bacteria numbers of the fresh fish is 5 x 105 cfu/g. It means that for total bacteria on using seaweed extract treatment can be received until the 36th storage time is 4 x 105 cfu/g.